IMPLEMENTASI MEDIA PEMBELAJARAN BLOG DAN CANVA PADA MATERI KAIDAH KEBAHASAAN TEKS BIOGRAFI DI SMK SEMARANG - Wulandari, Sri; Rifai, Ahmad; Wahyuni, Sri (Universitas Tanjungpura, 2024)
The study aims to describe the implementation of blog and Canva learning media on linguistic rules of biographical texts at SMK Semarang. The type of research used is a qualitative descriptive approach. The data from this research are the results of an analysis of the linguistic rules of the biographical text